MENGOPTIMALKAN POTENSI HEMISTER (OTAK KANAN) DALAM PROSES PEMBELAJARAN - Afrizal, Afrizal (STAI Hubbulwathan Duri, 2017)
The brain is the greatest gift of god for human. This brain consists of 2 parts. They are the right brain and left brain. Each part has a specific function. The right brain has a 90% memory capacity and left brain is only 10-12%. Recent research results was in the US said that the role of logic in making people become successful is only 4-6%, while 94-96% is determined by the right brain that associated alot with innovation, creativity, instinct, intuition, creativity, honesty, tenacity, responsibility, and others. In the learning process the balance of the two brains are very important to think optimally. Some of the efforts to optimize the right brain potential are Intelligent Movement, Game / Puzzle, Music, Social Communication and Hobby.